2019
DOI: 10.3389/fgene.2019.00148
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Persistence of Higher-Order Strand Symmetry in Genomic Sequences by Novel Word Symmetry Distance Analysis

Abstract: For the ubiquitous phenomenon of strand symmetry, it has been shown that it may persist for higher-order oligonucleotides. However, there is no consensus about to what extent (order of oligonucleotides or length of words) strand symmetry still persists. To determine the extent of strand symmetry in genomic sequences is critically important for the further understanding of the phenomenon. Based on previous studies, we have developed an algorithm for the novel word symmetry distance analysis. We applied it to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Previous studies of human DNA sequences have shown that, in accordance with CSPR, the frequencies of direct and reverse complement oligonucleotides are approximately equal up to oligonucleotides with 6 nucleotides. With increases to higher order oligonucleotides to 7, 8 and 9 nucleotides, the differences between the frequencies of D and RC(D) become bigger, and after oligonucleotides with 10 nucleotides, the frequency differences change radically and sporadically and gradually break down, instead of breaking abruptly [ 35 ]. As seen, the answer to the question of why oligonucleotides with 10 or more nucleotides do not satisfy CSPR is shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies of human DNA sequences have shown that, in accordance with CSPR, the frequencies of direct and reverse complement oligonucleotides are approximately equal up to oligonucleotides with 6 nucleotides. With increases to higher order oligonucleotides to 7, 8 and 9 nucleotides, the differences between the frequencies of D and RC(D) become bigger, and after oligonucleotides with 10 nucleotides, the frequency differences change radically and sporadically and gradually break down, instead of breaking abruptly [ 35 ]. As seen, the answer to the question of why oligonucleotides with 10 or more nucleotides do not satisfy CSPR is shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…For 11-nucleotide oligonucleotides, the CSPR analysis requires more than 6500 million nucleotides, i.e., the whole human genome would be too short. Such a gradual increase to longer DNA sequences for higher order oligonucleotides, because of the rapid growth of the number of oligonucleotide combinations, provides an explanation of why “the strand symmetry would break up gradually instead of breaking abruptly”, showing that strand symmetry persists for oligonucleotides of up to 9 nucleotides in the human genome for its oligonucleotide frequency pattern [ 35 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations